Nutrient uptake and growth response of the seagrass, enhalus acoroides (L.f.) royle to biodeposits of the giant clam, tridacna gigas (L.) in Bolinao, Pangasinan - Regino, Genevieve L. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2012)
The giant clam, Tridacna gigas and the seagrass, Enhalus acorroides are found together in a northern reef flat in Bolinao, Pangasinan.This study demonstrates that biodeposits from giant clams could enhance the growth of the seagrass seedlings. A series of experiments was done to determine the potential nutrient contribution of T. gigas biodeposits by quantifying biodeposit elimination, and the nutrients dissolved from T. gigas biodeposits. The change in nutrients and chlorophyll- concentration of ambient water in the presence of T. gigas was examined to determine balance between nutrient taken in by T. gigas and nutrients found in biodeposits. Results show that intermediate size giant clams (15-cm) produced 0.14 ± 0.02 g DW of biodeposits in 24 hours. Biodeposits had 3.5 ± 0.54 % carbon, 0.24 ±0.04 % nitrogen hence a C:N ratio of 14.37. Higher concentration of dissolved nitrogen compared to ambient seawater was seen in the biodeposits T. gigas took in dissolved nutrients and also removed chlorophyll-a. These results show that the input of T. gigas biodeposits augments the seagrass' sediment nutrient environment resulting in increased response of E. acoroides in terms of nutrition. The detection of changes in growth parameters, although small, could give an indication of the long-term effects of biodeposits. Limitations of this study are sample size and duration of the experiments.